Предмет: Математика, автор: solovevasona49

Помогите срочно!!!


Приложения:

Ответы

Автор ответа: pushpull
1

Ответ:

Пошаговое объяснение:

1

f(x) = x³ - x² - x

f'(x) = 3x² - 2x - 1

3x² - 2x - 1=0   ⇒ x₁= -1/3; x₂ = 1

2

f(x) = x\sqrt{12-x}

f'(x) = \frac{-3x+24}{2\sqrt{12-x} }

\frac{-3x+24}{2\sqrt{12-x} } = 0; x_1 = 8

3

f(x) = x - √2 * sinx

f'(x) = 1 -√2* cosx

1 -√2* cosx = 0; ⇒  x₁= π/4; x₂ = 7π/4

Похожие вопросы
Предмет: Русский язык, автор: zariii23234
Предмет: Биология, автор: nnnwww